Bihar Five-Year Plan Progress Report for the Period Ending March, 1956 - Planning Commission (Planning Commission, 1956)
Abstract of Expenditure up to 31st March 1956 Scheme wise Progress Agriculture Veterinary and Animal Husbandry Dairying and Milk-supply, Forests Co-operation, Fisheries, Rural Development Irrigation Projects Power Projects Cottage Industries.
Bihar